Alcohol industry sponsorship and alcohol‐related harms in Australian university sportspeople/athletes. (1st November 2012) - O'Brien, Kerry S.; Lynott, Dermot; Miller, Peter G.
Abstract: Introduction and Aims: Although there is evidence that alcohol sponsorship in sport is related to greater drinking, there is no empirical research on whether alcohol sponsorship is associated with alcohol‐related harms. We examined whether there is an association between receipt of alcohol industry sponsorship, and attendance at alcohol sponsor's drinking establishments (e.g. bars), and alcohol‐related aggression and antisocial behaviour in university students who play sport. Design and Methods: University sportspeople ( n = 652) completed surveys (response rate > 80%) assessing receipt of alcohol industry sponsorship, attendance at sponsor's establishments and confounders [i.e. age, gender, sport type, location and alcohol consumption measured by Alcohol Use Disorders Identification Test—alcohol consumption (AUDIT‐C) scores]. Participants also completed measures assessing displays and receipt of aggressive and antisocial behaviours (e.g. assaults, unwanted sexual advance, vandalism). Results: Logistic regression models including confounders and reported attendance at alcohol sponsor's establishments showed that sportspeople receiving alcohol industry sponsorship were more likely to have been the victim of aggression (adjusted odds ratio 2.62, 95% confidence interval 1.22–5.64). Attending an alcohol sponsor's establishment was not associated with higher rates of other aggressive or antisocial behaviour. However, significant associations where found between AUDIT‐C scores and having displayed and received aggression, and having damaged or had property damaged. Male sportspeople were more likely to have displayed and received aggressive and antisocial behaviour. Discussion and Conclusions: Higher AUDIT‐C scores, gender and receipt of alcohol industry sponsorship were associated with alcohol‐related aggression/antisocial behaviours in university sportspeople. Sport administrators should consider action to reduce the harms associated with excessive alcohol consumption and alcohol industry sponsorship in sport.